Immune Dysregulation in Children With Down Syndrome - Huggard, Dean; Doherty, Derek G.; Molloy, Eleanor J. (Frontiers in Pediatrics, 2020)
Down syndrome (DS) is the most common genetic syndrome associated with immune defects. The extent of immune dysregulation in DS is substantial, spanning the innate and adaptive systems and including anomalies in: T and B cells, monocytes, neutrophil chemotaxis, circulating cytokines, and suboptimal antibody responses which all contribute to an increased risk of infections, poorer clinical outcomes and chronic inflammation in this vulnerable cohort. Other aspects of innate immunity may also be abnormal and contribute to the increased morbidity and warrant further interrogation such as: gamma delta T cell function, the inflammasome, Toll-like receptors and their pathways. Pharmacotherapies such as pavilizumab, pneumococcal and influenza immunisations, as well as potential immunoprophylactic agents such as pidotimod, azithromycin and Brancho-Vaxam may help alleviate the infectious consequences. Children with DS need to be managed with a heightened sense of awareness and urgency in the setting of sepsis and signs of chronic inflammation need regular screening and appropriate follow up.